Comparison of vestibular ocular reflex and gross motor development in children with semicircular canal aplasia and hypoplasia. (November 2022) - Kimura, Yusuke; Kaga, Kimitaka
Abstract: Objective: To examine the effect of vestibular ocular reflex on gross motor development in children with semicircular canal aplasia and hypoplasia. Study design: Case series. Materials and methods: Children with congenital hearing loss underwent temporal bone computed tomography to assess their inner ear morphology. In this study, we examined eight children with bilateral complete aplasia of semicircular canals and seven children with bilateral hypoplasia of semicircular canals. Their vestibular ocular reflex was assessed using a damped rotational chair test. Their gross motor development was assessed by examining their ages of acquisition of head control and independent walking. Results: All eight children with semicircular canal aplasia were diagnosed as having CHARGE syndrome and five children were found to have CHD7 mutations. Cochlear morphological examination showed that cochlear hypoplasia type III was the most common in eight of 16 ears in children with semicircular canal aplasia. In semicircular canal hypoplasia, incomplete partition type II was found in seven of 14 ears. All eight children with semicircular canal aplasia showed no response in the damped rotational chair test. Even the three children followed up were unresponsive in all tests. In the group with semicircular canal hypoplasia, three children showed normal responses, one child showed no response, and three children showed poor responses. The mean age of acquisition of head control was 9.1 ± 6.3 months and that of independent walking was 31 ± 8.1 months in children with semicircular canal aplasia. The mean age of acquisition of head control was 6.0 ± 2.8 months and that of independent walking was 19.9 ± 4.9 months in children with semicircular canal hypoplasia. Conclusions: We found that children with semicircular canal aplasia have severe dysfunction of the vestibular ocular reflex, and vestibular sensory cells derived from the semicircular canal may not be present. Semicircular canal hypoplasia is associated with dysfunction of the vestibular ocular reflex, but vestibular sensory cells may be present, and rotary nystagmus develops with growth similar to that observed in normal children previously reported. Semicircular canal aplasia is associated with CHARGE syndrome, and affected children tended to have a slower gross motor development. It was suggested that the combination of visual impairment and mental retardation may delay the development of central-level integrated functions and may further delay motor development.